Efficacy and safety of darolutamide versus abiraterone acetate plus prednisone in combination with ADT for mHSPC: a real-world clinical retrospective study - Ting Hu; Ting Hu; Fang Zhou; Yang Zheng; Yang Zheng; Bohan Luo; Bohan Luo; Yongliang Zhang; Chengpeng Gu; Chengpeng Gu; Guopeng Wang; Guopeng Wang; et al. (Frontiers in Pharmacology)
IntroductionEffective treatment during the metastatic hormone-sensitive prostate cancer (mHSPC) stage is crucial for delaying disease progression. Due to the lack of a head-to-head comparison of darolutamide (DARO) and abiraterone acetate plus prednisone (AAP) doublet regimen, this study aims to compare the efficacy and safety of DARO + ADT and AAP + ADT in the treatment of mHSPC in the real world.MethodsThis study retrospectively analyzed patients with mHSPC who received DARO or AAP treatment in Sichuan Provincial People’s Hospital from January 2022 to June 2024, with follow-up until December 2024. The clinical data and prostate-specific antigen (PSA) changes of patients were collected. The primary endpoint was time to metastatic castration-resistant prostate cancer (mCRPC), and the secondary endpoints were overall survival (OS), radiological progression-free survival (rPFS), time to PSA progression, time to pain progression, and time to subsequent prostate cancer therapy.ResultsA total of 178 patients were included, with 96 in the DARO group and 82 in the AAP group. The baseline characteristics of the two groups were comparable. The median follow-up time and interquartile ranges of the DARO and AAP groups were 12.0 [7.9–17.6] months and 17.4 [9.3–23.8] months, respectively. For the primary endpoint, DARO significantly delayed the time to mCRPC versus AAP [HR, 0.41 (95%CI, 0.23 to 0.71); P < 0.005]. And the DARO group significantly benefited in all secondary endpoints. DARO significantly led to deeper PSA reduction compared to AAP, with higher median reduction rates, better PSA50 and PSA90 remission rates, and a higher proportion of patients reaching lower PSA values. The incidence of adverse reactions was similar in the two groups, and there was no grade 3 or above drug-related adverse reactions.ConclusionIn the treatment of mHSPC, DARO + ADT was associated with significant improvement of clinical outcomes versus AAP + ADT, while their safety is comparable.